Outcome of congenital heart diseases in Egyptian children: Is there gender disparity? - Zeze Thabet Atwa; Hebatallah Hsan Safar (SpringerOpen, 2014)
The purpose of this work is to evaluate the effect of sex on the outcome of congenital heart diseases (CHDs) in children. The frequency of occurrence of each outcome within the disease is also detected. Methods: 312 patients (171 males and 141 females) with CHDs aged less than 12 years were included in this study. For them complete history taking, physical examination, chest X-ray, electrocardiography and echocardiography were done. The following aspects were recorded: mortality, surgical repair, development of pulmonary hypertension, diagnosis of heart failure, hospitalization due to chest infection and growth parameters (weight and height). Results: Of 312 patients the most frequent two diagnoses were atrial septal defect (28.8%), and ventricular septal defect (28.2%). Death occurred in 4.8% of patients with no significant gender difference. 11.9% of patients were treated surgically with no sex disparity. 23.1% developed heart failure and 34.9% of the patients developed pulmonary hypertension with no significant sex difference. 35.6% and 34.6% of the patients were below 10th percentile for weight for age and height for age, respectively with no sex difference. Hospitalization due to chest infection occurred in 42.9% of the patients; females had significantly higher risk than males. Conclusion: Females are more vulnerable to hospitalization due to chest infection than males in children with congenital heart diseases while as regards mortality, access to surgery, occurrence of heart failure, development of pulmonary hypertension and affection of growth, no significant gender differences were detected.